2018
DOI: 10.1016/j.jjcc.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Transcaval approach for endovascular aortic interventions: A systematic review

Abstract: The caval-aortic path is a novel access route for endovascular aortic interventions in aortic interventions, particularly for patients unsuitable for traditional access routes including femoral, subclavian, transapical, and aortic. A systematic review was conducted as per the PRISMA guidelines utilizing three electronic databases: Medline, Embase, and Cochrane database. There were 10 studies identified, including 7 retrospective studies, 1 prospective cohort study, and 2 case reports. Data on 209 patients (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…In addition, references related to this subject but very narrative and repetitive were removed. Finally, 25 reports were selected: three on the access route technique [ 6 - 8 ] , one experimental study [ 9 ] ; three cohort references (one retrospective and two prospective) for TAVI [ 10 - 12 ] ; two cases on TC access for TAVI through a conventional aortic graft [ 13 , 14 ] ; one case on TC access for TAVI through partially thrombosed infrarenal aortic aneurysm [ 15 ] ; one case on TC access for TAVI in a patient with duplicated inferior vena cava [ 16 ] ; one case on TC access for Biventricular Impella placement [ 17 ] ; eight references on six cohorts (retrospective) on the treatment of type II endoleaks after EVAR [ 18 - 25 ] ; two cases on treatment of type I endoleaks after EVAR and after chimney endovascular aneurysm repair (ChEVAR) respectively [ 26 , 27 ] ; two cases on thoracic endovascular aneurysms repair (TEVAR) [ 28 , 29 ] ; and one systematic review on the transcaval access to the aorta [ 30 ] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, references related to this subject but very narrative and repetitive were removed. Finally, 25 reports were selected: three on the access route technique [ 6 - 8 ] , one experimental study [ 9 ] ; three cohort references (one retrospective and two prospective) for TAVI [ 10 - 12 ] ; two cases on TC access for TAVI through a conventional aortic graft [ 13 , 14 ] ; one case on TC access for TAVI through partially thrombosed infrarenal aortic aneurysm [ 15 ] ; one case on TC access for TAVI in a patient with duplicated inferior vena cava [ 16 ] ; one case on TC access for Biventricular Impella placement [ 17 ] ; eight references on six cohorts (retrospective) on the treatment of type II endoleaks after EVAR [ 18 - 25 ] ; two cases on treatment of type I endoleaks after EVAR and after chimney endovascular aneurysm repair (ChEVAR) respectively [ 26 , 27 ] ; two cases on thoracic endovascular aneurysms repair (TEVAR) [ 28 , 29 ] ; and one systematic review on the transcaval access to the aorta [ 30 ] .…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the systematic review by Wee et al [ 30 ] summarized the current status of this subject: "TC approach for endovascular aortic interventions for patients unsuitable for traditional access routes". The authors described the outcome of 209 patients (TAVI, type II endoleaks and TEVAR) with a mean age of 79.5±5.1 years and 51.2% men.…”
Section: Methodsmentioning
confidence: 99%
“…A recent meta-analysis concluded that the initial evidence is encouraging but further prospective studies are probably required before any firm conclusions can be made. 34 In general, vascular access site complications are a common cause of significant morbidity and mortality after a TAVI procedure. A key role of the heart team should be to identify the access route that will minimise this risk.…”
Section: Transcavalmentioning
confidence: 99%
“…In the setting of cardiac arrest, arterial access is crucial for delivery of mechanical circulatory support devices such as an Impella CP ® (Abiomed, Danvers, MA, USA) or cannulation for extracorporeal cardiopulmonary resuscitation (ECMO) 1 , 2 . When the femoral artery is inaccessible due to iliofemoral atherosclerosis, tortuosity, calcifications, abdominal aneurysm, or previous surgery, other approaches should be considered 3 . Transcaval/caval-aortic and percutaneous axillary artery access have both been proven safe alternative access in patients undergoing transcatheter aortic valve replacement (TAVR) for severe aortic stenosis 3–5 …”
Section: Introductionmentioning
confidence: 99%
“…When the femoral artery is inaccessible due to iliofemoral atherosclerosis, tortuosity, calcifications, abdominal aneurysm, or previous surgery, other approaches should be considered 3 . Transcaval/caval-aortic and percutaneous axillary artery access have both been proven safe alternative access in patients undergoing transcatheter aortic valve replacement (TAVR) for severe aortic stenosis 3–5 …”
Section: Introductionmentioning
confidence: 99%